(3JMbjb GdNdGa aj CUMGH GdCYQGas - (3eQYj Hf jhSa Hf CHj HcQ Hf CMeO GdcQej GdebOSj GdMfHdi,J (B1033 (3g` s
(3ChdgG (B:s
(3GdMeO ddg Pi GdYOd hGdEfUGa CeG HYO ajbhd bO ESJNQJ Gddg JYGdi SGFdkG Yahg hZaQGfg ai JdNjU aQGFO JJYdb HGdcdGe Ydi CUMGH GdCYQGa heG bGdg ajge Cgd GdJaSjQ hGdMOjK ef GdNdGa hSejJg JMbjb GdNdGf ebOeg ai GdcdGe Ydi GdCYQGa s
(3BNQgG (B:s
(3hbjd Cfge jUjQhf JQGHkG aUGQ MGUd eG ajge ef GdNdGa SHYI CbhGd hbO PcQJ Odjd cd bhd efgG hdjS bUOfG gfG EdG HjGf MGd CUMGH GdCYQGa hGeG gPG aHWQjb GdYQV hGddg SHMGfg CYde hUdi Gddg Ydi SjOfG eMeO NGJe GdCfHjGA hGdeQSdjf hYdi Bdg hUMHg CLeYjfs
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B15s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B203 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B12 - (3U (B218s
(3eUOQ GbJfGA GdCUd (B:s
(3GdeOQSI GdCMeOjI (B_ (3GdehUd (B(115) s
Keywords: (3GdeLGejYs